Impact of Different Types of Physical Exercises for the Management of Older Women with Urinary Incontinence: A Systematic Review of Randomized Clinical Trials - da Rocha, Waleska Souza; Reis-Silva, Aline; Coelho-Oliveira, Ana Carolina; Moura-Fernandes, Marcia Cristina; da Silva Alves Cunha, Rosane; Alhammad, Ayman; de Sá-Caputo, Danúbia da Cunha; Bernardo-Filho, Mario; Taiar, Redha (Journal of Clinical Medicine, 2025)
Background/Objectives: Urinary incontinence (UI) is particularly prevalent in women of all ages, but especially in older women, due to risk factors that contribute to pelvic floor muscle weakness. Urinary incontinence can have a significant psychosocial impact and compromise the quality of life of affected women. It is reported that physical activity seems to be inversely associated with UI. The aim is to summarize the impact of different modalities of physical exercises in management of older women with UI. Methods: Searches were performed in the databases PubMed, Web of Science, EMBASE and Scopus. The searches were performed on 10 December 2024. Only randomized clinical trials were included. Ninety-three papers were initially screened, and five full papers reached all the inclusion criteria describing the effects of exercise on urinary incontinence. The studies included a total of 352 elderly participants aged 60 years or older. Of these participants, 268 lived in nursing homes and 84 lived in a local community. The intervention period varied among the selected studies from 6 weeks to 12 months, and in general, the pelvic floor training was used. Results: Improvements in the quality of life and in the physical performance of the older women with UI were reported, although the risk of bias was classified as “some concerns”. Conclusions: Moreover, it is revealed that different types of exercises are used to “work” the pelvic floor muscle and contribute, in general, to reducing the symptoms, and improving the quality of life of older women with UI due to the positive impact of the exercises.
Number: 10
Keywords: pelvic floor muscle; physical performance; quality of life; urinary incontinence